Disease Resistance Attributes Conferred by Mineral Fertilizer in Dioscorea Species - Otusanya, M. O. (European Journal of Applied Sciences, 2021)
This study investigated proximate content, phenol as well as mineral content effects of an 8-mineral content fertilizer, namely Bounty, on resistance attributes in the nourished tubers of four Dioscorea species varieties, compared to those sourced from farmers plots within Ogun state, which had been nourished with the natural replenishment of at least 2 to 4 years fallow. The experiment was a 4 by 3 factorial arranged in RCBD (randomized complete block design) with 12 treatment combinations and 3 replicates. Main factor was variety that is Dioscorea rotundata varieties Oniyere (from South West Nigeria) and Abuja (from middle belt Benue/Plateau of Nigeria), D. cayenensis var. Igangan/Alo (from South West Nigeria) and Dioscorea alata var. Agbodo (from South West Nigeria). Treatments were Bounty fertilizer at the rates 0.6 ml l–1 as well as 1.2 ml l–1 and farmers’ plot (FPT, with no fertilizer). The Bounty-fertilized tubers were harvested from the Teaching and Research Farms of the Directorate of University Farms, Federal University of Agriculture, Abeokuta, Ogun State, Nigeria at 6 months after planting (6 MAP). Farmers plot tubers were also harvested at 6 MAP. Analysis was done after processing of the tubers. Among the proximate components, moisture, dry matter, ash, crude fibre and carbohydrate of mean values 14.05%, 85.96%, 2.77% dm, 8.55% dm and 82.71% dm were comparable/similar in the four varieties. However, Oniyere (white guinea yam – South West Nigeria) was lower in fat and higher in crude protein than the other three varieties. Abuja, Igangan and Agbodo were comparable/similar in fat content, but Igangan (yellow guinea yam) had lower crude protein than Agbodo (water yam) whereas Abuja (white guinea yam – Middle Belt Nigeria) and Agbodo were similar/comparable in crude protein. Bounty-fertilized tubers at the 2 concentrations were lower in ash (mean 2.63% dm) and carbohydrate (80.98% dm) than Farmers plot tubers (FPT), (3.06 and 86.17% dm respectively). But they were higher in phenol and calcium, with means of 189.82 and 22.16 mg/100 g dm respectively than farmers plot tubers (means of 120.77 and 16.89 mg/100 g dm). Both calcium and phenol have been reported in increased resistance to disease in plants including Dioscorea spp. in literature. Correlation tests in this study indicated significance between calcium (from the fertilizer) and tuber phenol (r = 0.4523). Calcium correlated significantly also with crude fibre (r = 0.9325) and crude fibre with phenol (r = 0.7110). Calcium correlated significantly also with tuber potassium which was not supplied from the fertilizer (r = 0.6662), indicating that increased uptake of calcium would enhance uptake of potassium. Consequently potassium supported by Nitrogen (the highest component, 15% w/w in Bounty Fertilizer) would have positive effect on tuber yield, as the highest proportion (91% to 94%) of total N and K are reported to be accumulated in yam tubers at harvest. These results underscore effects of mineral nutrition (such as Bounty) for increased disease resistance and increased yield, over natural replenishment after fallow which the smallholder farmer depends on solely in Nigerian traditional yam farming system.